Muscle Activity of the Upper and Lower Body Part in Car Gearing Action: A Preliminary Study / Nor Kamaliana Khamis...[et al.] - Khamis, Nor Kamaliana; Md Deros, Baba; Nawawi, Roslizawati; Saleh, Chairul (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Understanding of the muscle activity and its activation in driving task is very important. It can provide more knowledge to study the effects on the muscle when performing different driving styles task within certain duration. The main objective of this study is to investigate the role of the main parts in shoulder and leg with regards to certain driving condition when performing gearing action. In this study, the two main muscle parts selected were deltoid anterior (DA) and gastrocnemius medialis (GM) and used a simulator with manual transmission. Two female subjects with more than three years driving experience participated in this study and they were required to drive the car simulator for 15 minutes. The Electromyography (EMG) signals were recorded during pre-driving and post-driving tasks. Research findings showed the left DA muscle has significant difference with respect to the signal pattern when changing and holding the gear from free gear to gear 1 and to gear 2. Meanwhile, the right DA and the left GM showed no significant different in its activation between each gear action. The finding of study can contribute towards improving driver’s driving behavior and style. In addition, it can be used to incorporate ergonomics approach in the design of the car gearing system.